Pengaruh Kinerja Keuangan terhadap Kemampuan Membayar Zakat PT. BRI Syariah Periode 2011-2018 - Ritonga, Budi Yanti; Siregar, Budi Gautama; Windari, Windari (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Padangsidimpuan, 2020)
Islamic financial institutions including PT. BRI Syariah from the financial statements determines the amount of zakat of the company because in Islam one of the objectives of financial reporting is for the purposes of zakat. This research is a quantitative research. The collection technique used in this study was secondary data as many as 32 samples. The data collection technique is documentation. The data analysis technique used multiple linear regression methods, classical assumption tests, and hypothesis testing with data processing using the SPSS version 23 computer program. The results of the study partially (t test) stated that, ROA had a significant effect on the ability to pay zakat. ROE has a significant negative effect on the ability to pay zakat. BOPO has a significant negative effect on the ability to pay zakat. Simultaneous research results (F test) states that ROA, ROE and BOPO affect the ability to pay zakat. While the results of the coefficient of determination (R2) ROA, ROE and BOPO are able to influence the ability to pay zakat. Keywords: ROA, ROE, BOPO, Ability to Pay Zakat